2011
DOI: 10.1111/j.1365-2966.2011.19886.x
|View full text |Cite
|
Sign up to set email alerts
|

Excitation of unidentified infrared bands by H atom impacts

Abstract: A model was developed for the excitation of the unidentified infrared bands (UIBs) by H atom impacts in the interstellar medium. It builds upon the fact that, in the presence of far‐ultraviolet (far‐UV) radiation and hydrocarbon grains, the hydrogen gas will be partially dissociated and the grain surface will be partially hydrogenated and partially covered with free C bonds. Under such a statistical equilibrium, H atoms from the gas will recombine with C atoms at the grain surface at some rate. At each recombi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 47 publications
1
4
0
Order By: Relevance
“…According to the literature, the C–O vibrational mode contributes to the UIR between 6 and 6.5 μm in the case of an O-bridge between two aromatic groups, 52 and at 6.2, 7.7 and 8.6 μm in cases of C–O functional groups in molecules composed of C, H, O, N and S atoms. 53,54 A careful analysis of the C–O stretching modes for studied compounds showed that their contribution fell between 7.4 and 9.2 μm, which compares well with the literature. The agreement between the observational characteristics of UIR features and molecular vibrational contributions reported herein implied that dicyanofurans and their protonated forms had a high chance to be detected in the ISM.…”
Section: Resultssupporting
confidence: 86%
“…According to the literature, the C–O vibrational mode contributes to the UIR between 6 and 6.5 μm in the case of an O-bridge between two aromatic groups, 52 and at 6.2, 7.7 and 8.6 μm in cases of C–O functional groups in molecules composed of C, H, O, N and S atoms. 53,54 A careful analysis of the C–O stretching modes for studied compounds showed that their contribution fell between 7.4 and 9.2 μm, which compares well with the literature. The agreement between the observational characteristics of UIR features and molecular vibrational contributions reported herein implied that dicyanofurans and their protonated forms had a high chance to be detected in the ISM.…”
Section: Resultssupporting
confidence: 86%
“…The molecules and clusters that are too small to reach an equilibrium temperature can be shown to emit, through a different mechanism, a spectrum which differs from a graybody spectrum (see Papoular 2012 and. This spectrum extends over the phonon continuum but is weaker than the gray-body spectrum modeled above.…”
Section: Discussionmentioning
confidence: 95%
“…We consider here the possibility that part of it might be due to grain heating by capture of wandering H atoms. This heating agent was studied in detail in Papoular (2012), where it was shown to be effective in the case of hydrocarbon grains with dangling carbon bonds, i.e. not capped with a hydrogen atom.…”
Section: Excitation and Fluctuation Of Dust Emissionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some alternative mechanisms, such as the release of chemical energy (Duley and Williams, 2011) and atom impacts (Papoular, 2012), have been introduced to explain the excitation of AIBs. It remains unknown whether these mechanisms play a role on the excitation of C 60 IR bands.…”
Section: Refmentioning
confidence: 99%